But Where Will the Money Come From? Experts' Views on Revenue Options to Implement Campaign for Fiscal Equity v. State of New York - Osnat Zaken; Jeffery E. Olson (Educational Considerations, 2013)
In 2003, the New York State Court of Appeals, the highest court in New York, upheld a trial court decision that funding for public education in New York City was unconstitutional and decreed that the state needed to increase operating aid to school districts by 5.6 billion per year (Campaign for Fiscal Equity, Inc. v. State of New York 2003).
Keywords: recommendations; money; revenue; options; implement; New York; Campaign; Fiscal Equity; tax; Institute; policy